Canine paroxysmal dyskinesia—a review - Mandigers, Paul J. J.; Santifort, Koen M.; Lowrie, Mark; Garosi, Laurent (Frontiers in Veterinary Science, 2024)
Paroxysmal dyskinesias (PDs) are a group of involuntary, hyperkinetic movement disorders that recur episodically and may last seconds to hours. An important feature of PD is that there is no loss of consciousness during the episode. Using a clinical classification three main types of PD have been distinguished in canine PD: 1) paroxysmal kinesigenic dyskinesia (PKD) that commences after (sudden) movements, 2) paroxysmal non-kinesigenic dyskinesia (PNKD) not associated with exercise and can occur at rest, and 3) paroxysmal exertioninduced dyskinesia (PED) associated with fatigue. Canine PDs are diagnosed based on the clinical presentation, history and phenomenology. For the latter, a video recording of the paroxysmal event is extremely useful. An etiological classification of canine PDs includes genetic (proven and suspected), reactive (drug-induced, toxic, metabolic, dietary), structural (neoplasia, inflammatory and other structural causes), and unknown causes. In this review an overview of all reported canine PDs is provided with emphasis on phenotype, genotype, and, where possible, pathophysiology and treatment for each reported canine PD.